Identification of potential long noncoding RNA associated with nasopharyngeal carcinoma using deep sequencing. Issue 7 (July 2019) - Xu, Yu-Zhong; Chen, Fang-Fang; Zhang, Yu; Liang, Hui; Li, Xiao-Jun; He, Chen
Objective: To identify differentially expressed long noncoding RNAs (lncRNAs) in nasopharyngeal carcinoma (NPC) compared with chronic nasopharyngitis (CNP) tissues. Methods: This prospective cohort study enrolled patients with NPC and CNP. The levels of lncRNAs in NPC and CNP tissues was detected by deep sequencing and quantitative polymerase chain reaction. Kyoto Encyclopedia of Genes and Genomes pathway analysis and antisense prediction were performed to reveal the function of differentially expressed lncRNAs (DELs). Receiver operating characteristic (ROC) curve and correlation analyses were used to evaluate the clinical and prognostic value of lncRNAs. Results: A total of 30 NPC and 27 CNP tissues were analysed. A total of 296 DELs were identified. LncRNAs ENSG00000227084 and ENSG00000230489 might play important roles in the development of NPC by interfering with the Rap1 signalling pathway and natural killer cell-mediated cytotoxicity, respectively. Antisense prediction showed that lncRNA ENSG00000230489 was paired with VAV3 mRNA. LncRNAs ENSG00000230489 (area under the ROC curve = 0.9138) and ENSG00000227084 (area under the ROC curve = 0.8037) may be diagnostic markers for NPC. Furthermore, low levels of ENSG00000230489 was positively associated with distant metastasis. Conclusion: LncRNAs ENSG00000230489 and ENSG00000227084 may be potential diagnostic markers and therapeutic targets for NPC.